Pelaksanaan Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perdesaan Dalam Meningkatkan Kesejahteraan Masyarakat Miskin di Desa Sukarara Kecamatan Jonggat Kabupaten Lombok Tengah - Raddana Raddana (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2015)
Abstract: Empowerment is an attempt to make people, groups or communities become more empowered so that they can take care of their interests independently. As we know, that in the implementation of PNPM-MP should involve community participation as an essential element. However, the implementation in the field, PNPM-MP faced with the problem of minimal participation of the community. This will result in less optimal implementation of PNPM-MP in Sukarara, Jonggat, Central Lombok. The writer interested in conducting research with the title of PNPM-MP in Improving Welfare of the Poor with the formulation of the problem: (1) How is the implementation (2) What are the barriers and factors supporting the implementation and (3) what the government's efforts to overcome obstacles of PNPM-MP in improving the welfare of the poor in Sukarara, Jonggat, Central Lombok.This study uses descriptive qualitative research method, the writer did not use the sample population. The writer is using purposive informants as a source of primary data and documents as a source of secondary data. To support ongoing research, writer uses a variety of secondary data in order to support the completeness of the data required in this study.The results of the study: (1). PNPM-MP can be broadly improve the welfare of the poor due to open employment opportunities through development of infrastructure. (2). Barriers in general practice: Human resources is still low, procurement of materials/goods to be auctioned, disbursements are often not timely, lack of socialization and development and (3) Supporting the management of the program is already well organized from the central, provincial, regency, districts and villages (4) efforts by the government is directing the public to increase their knowledge and skills.Keywords: Implementation, PNPM-MP, Welfare of the Poor